Emotional Experience of Orphanage Staff in Caring for Aggressive ODGJ: Nina Sunarti, Fitria Prihatini - Nina Sunarti; Fitria Prihatini (STIKes Persada Husada Indonesia, 2026)
Research Objective: This study aimed to explore the emotional experiences, coping responses, and support needs of orphanage or social-care staff who care for people with mental disorders (ODGJ) exhibiting aggressive behavior. Methodology: This qualitative study used a phenomenological approach. Eight orphanage staff members with direct experience in caring for aggressive ODGJ were recruited through purposive sampling at one social-care institution in Bekasi, West Java. Data were collected through in-depth semi-structured interviews and field notes. The data were analyzed using thematic analysis, including familiarization, coding, categorization, theme development, and theme refinement. Trustworthiness was strengthened through credibility, dependability, confirmability, and transferability strategies. Results: Five major themes were identified: initial encounters with aggressive behavior, emotional responses to aggression, strategies for managing emotions, meaning-making and empathy development, and expectations for institutional support. Participants described feelings of fear, anxiety, tension, hypervigilance, and concern for safety. However, through experience, they also developed patience, calming communication, teamwork, emotional control, and empathy. Conclusion: Caring for aggressive ODGJ is emotionally demanding and may lead to fear, anxiety, emotional exhaustion, and occupational stress among orphanage or social-care staff. The findings highlight the need for organizational support, structured training, psychological assistance, and clear institutional policies. Strengthening staff resilience and burnout-prevention strategies is essential to improve staff well-being and the quality of care for ODGJ in social-care institutions.